2011
DOI: 10.3844/ajassp.2011.1067.1072
|View full text |Cite
|
Sign up to set email alerts
|

Catch Composition of Tsetse Flies (<i>Glossina: Glossinidae</i>)

Abstract: Problem statement:A study to determine the composition of tsetse flies species was conducted between January and December, 2007 in Kamuku National Park, Nigeria, using Biconical and Nitse traps. Tsetse flies were trapped along gallery forest in five streams for two trapping days and were collected daily. Approach: All tsetse flies caught were identified to species level, sexed, separated into teneral and non-teneral, hunger staged and Mean Hunger Stage computed. Fly density were calculated, the age structure e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, a decrease in temperature slows down the rate of eggs development in the ovaries and increases the larval period leading to the inactivation of Glossina males rendering them unable to fertilize Glossina females which eventually could cause to population density drop-off (Mellanby, 1937); Moreover, the low fly apparent density in the wet season might be due to the presence of full leafed vegetation, which implies that many areas became water-logged and could attract predators such as spiders, dragonflies and ants on tsetse fly. Consequently, this might have forced the flies away from riverine vegetation into the open woodland (Okoch et al, 2011). Flies disperse beyond the water courses during the wet season is on contrary to the report in which flies disperse along river banks during wet seasons (Cano et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, a decrease in temperature slows down the rate of eggs development in the ovaries and increases the larval period leading to the inactivation of Glossina males rendering them unable to fertilize Glossina females which eventually could cause to population density drop-off (Mellanby, 1937); Moreover, the low fly apparent density in the wet season might be due to the presence of full leafed vegetation, which implies that many areas became water-logged and could attract predators such as spiders, dragonflies and ants on tsetse fly. Consequently, this might have forced the flies away from riverine vegetation into the open woodland (Okoch et al, 2011). Flies disperse beyond the water courses during the wet season is on contrary to the report in which flies disperse along river banks during wet seasons (Cano et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…The existence of a large fly catches caught in Nyawa stream, KKC during the study period might be due to the presence of dense vegetation of tall shaded trees along this stream which provides shade and maintains a suitable microclimate for tsetse as well as a habitat for their vertebrate hosts. Such environmental parameters have created suitable conditions for the survival and flourishing of flies (Rogers and Randolph, 1985;Okoch et al, 2011). This study showed a disparity in the higher number of male fly catches as compared with the number of female fly catches.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As expected, the overall prevalence of trypanosome infections was lower in tsetse flies than in cattle mostly because one tsetse fly can transmit trypanosomes to more than one animal. This finding could also be due to the fact that majority of trapped tsetse flies are comprised of unfed flies [ 46 , 47 ], which normally have a lower chance of carrying trypanosome infections. The epsilon traps used in this study are known to be selectively specific to savannah tsetse flies ( G. pallidipes and G. morsitans ) and hence may leave out other tsetse fly species responsible for transmitting some species of trypanosomes [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, 80% of total land area is infested with tsetse flies; moreover, biting flies, particularly of the genera Tabanus and Stomoxys , are thought to be ubiquitous (Dipeolu, ; Ahmed, ; Ahmed et al ., ; Okoh et al ., ; Odeniran et al ., ). The southwest of Nigeria is a marketing area for livestock owners and is subject to continuous migration and transhumance, as well as pastoral settling (Abubakar et al ., ).…”
Section: Introductionmentioning
confidence: 97%